Exploring HRM involvement in CSR: variation of Ulrich's HR roles by organisational context. Issue 21 (30th November 2021) - Sarvaiya, Harsha; Arrowsmith, Jim; Eweje, Gabriel
Abstract: The nascent literature around corporate social responsibility (CSR) and human resource management (HRM) suggests considerable involvement of HR in the development and implementation of CSR strategy, but there is a lack of consensus around the extent, contingencies and theoretical assumptions underpinning such an emerging role. This study examines how far and under what circumstances HR is engaged in CSR strategy formulation and implementation. Drawing on data from interviews with 29 HRM and CSR professionals in 16 New Zealand organisations, we found that the CSR–HRM relationship varies according to organisational context, including the stage of CSR development and sector, and according to how far the remit of CSR extends to 'internal' as well as 'external' considerations. Within a multi-dimensional CSR–HRM relationship and context, HRM is likely to provide considerable strategic and operational input to the development and implementation of 'internal CSR', the natural domain of HRM relating to employee development and well-being. Utilising Ulrich's model of HRM, the analysis also finds evidence of the roles of administrative expert, employee champion and change agent in relation to external CSR, though the focus is more on support than 'strategic partnership' in this domain. Hence, the role of HR in CSR is multi-faceted and varies according to organisational contextual factors. The paper concludes with implications for HR management and avenues for further research.